Development and characterization of treated kaolin filled polypropylene/kaolin nanocomposites - Yahaya, Shehu (2018)
This research work focused on producing modified kaolin filler in polypropylene/kaolin (PP/K) nanocomposite by melt compounding process in order to improve its mechanical and thermal properties for industrial applications. The surface treatments of micron sized Malaysian kaolin were conducted to produce nano sized kaolin by acidification of kaolin fillers with sulphuric acid and planetary milling using urea (mechanochemical milling). Testing on both surface treated kaolin were carried out with the aid of Field Scanning Electron Microscopy (FESEM), Fourier Transform Infrared (FTIR), Brunauer–Emmett–Teller (BET), X-ray Diffraction (XRD) and Particle Size Analyser and results of both treated kaolin were compared. However, the surface treated kaolin using acidification was unsuccessful as shown by XRD, FTIR and BET results. A successful delamination of micron sized into nano sized kaolin was achieved by mechanochemical milling. The additional bands at 3624, 3445 and 3388 cm-1 and illite phase at lower 2θ by FTIR and XRD studies respectively, indicated delamination of kaolin. Surface area increased by 400% from BET results. The PP/K nanocomposite was produced by incorporating low weight (1-7%) percentages of organically modified nanokaolin into PP by melt compounding with polypropylene grafted maleic anhydride (PP-g-MA) as coupling agent. The FTIR and XRD analyses on chemical structure showed successful synthesis of PP/K nanocomposites by the vanishing of characteristic of OH bands and peaks of kaolin respectively. The tensile and impact strength, tan δ, loss modulus and melt flow index of PP/K nanocomposite decreases by 17, 27, 36, 32 and 78% respectively. Conversely, the results show that incorporation of nanokaolin clay into PP causes increase in thermal degradation (200%), crystalinity (17%), nucleation effect (17%), storage modulus (10%), surface roughness (87%), and optical (262%). Whereas, TEM of PP/K nanocomposite exhibit nanokaolin dispersion with nanoscale sizes. Therefore, the PP/K nanocomposites formulated shall be a potential candidate for manufacturing novel new materials of attraction in many sectors.